Almanac 2012—adult cardiac surgery: the national society journals present selected research that has driven recent advances in clinical cardiology. Issue 19 (10th September 2012) - Bridgewater, Ben
Abstract : This review covers the important publications in adult cardiac surgery in the last few years, including the current evidence base for surgical revascularisation and the use of off-pump surgery, bilateral internal mammary arteries and endoscopic vein harvesting. The changes in conventional aortic valve surgery are described alongside the outcomes of clinical trials and registries for transcatheter aortic valve implantation, and the introduction of less invasive and novel approaches of conventional aortic valve replacement surgery. Surgery for mitral valve disease is also considered, with particular reference to surgery for asymptomatic degenerative mitral regurgitation.